TURBULENT CHARACTERISTICS OF SHALLOW FLOW OVER ROUGH SURFACE WITH REGULARLY ARRAYED SPHERES - Sukarno, - (JURNAL ILMIAH MEDIA ENGINEERING, 2013)
Turbulent nature of near-bed flow field was investigated in an open channel over a rough-bed artificially arrayed with glass beads, where ratios of the glass diameter to flow depth are 0.3, 0.5 and 0.8. Detailed spatial measurements of streamwise and vertical velocity fluctuations were made using Particle Image Velocimetry (PIV) in a vertical plane along the completely rough bed surface. Results indicated significant degrees of spatially regular variation in the time-averaged velocities, in which the upflow generated over upper region of roughness top is about 8% of the cross sectional average velocity, much stronger than the downflow. In addition, Reynolds shear stress and turbulent intensity showed minimum values at the ridge of roughness elements and maximum ones at the trough. These organized flow structure were suggested to be due to the vortex shedding brought about by the roughness elements.Keywords: turbulent characteristics, bed-flow, streamwise, velocity, roughness